Grazing and phosporic fertilizer evaluation on intercropped pastures (Cynodon nlemfluensis) and (Arachis pintoi). - Barrios, Byron; Hernández, M.; Valdez, W. (Agronomía Mesoamericana, 2016)
A study was conducted to determine the grazing period (grazing + recovery) and the optimal dose of phosphate fertilization in the associaation Cynodon nlemfluensis and Arachis pintoi (CIAT 17434). The study was conducted at Centa experimental station, located at lzalco, El Salvador. It was concIuded that these two species growing together can be grazed each 14 days with two days of actual grasing. At least 12.9 kg/ha of phosphorus/ha/year is needed. The system withstands an animal load of 2406 kg/ha/year. Controlled defoliation each 14 days, stimulates vegetative growth of Arachis pintoi (CIAT 17434).